Inhibition of Skp2 enhances doxorubicin‐induced cell death in B cell precursor acute lymphoblastic leukemia. (13th March 2022) - Manafi Shabestari, Rima; Chegeni, Rouzbeh; Faranoush, Mohammad; Zaker, Farhad; Safa, Majid
Abstract: S‐phase kinase‐associated protein 2 (Skp2) is a well‐defined component of the Skp2‐Culin1‐F‐box (SCF) E3 ubiquitin ligase complex, which is involved in cell cycle progression and considered a prognostic marker in cancers. Overexpression of Skp2 is frequently observed in patients with acute lymphoblastic leukemia (ALL). Inhibition of this protein may be a valuable strategy to induce apoptosis in malignant cells. Less well known is the effect of Skp2 inhibition on the potentiation of the chemotherapeutic‐induced cell death in B cell precursor acute lymphoblastic leukemia (BCP‐ALL). Our results demonstrated that inhibition of the Skp2 using SZL P1‐41, not only resulted in caspase‐mediated apoptosis but also potentiated doxorubicin‐induced apoptosis in BCP‐ALL cell lines (NALM‐6 and SUP‐B15). SZL P1‐41 in combination with doxorubicin altered cell cycle distribution and the level of cyclins and cyclin‐dependent kinases in BCP‐ALL cells. DNA damage response genes were also upregulated in presence of the doxorubicin and SZL P1‐41 in both cell lines. In conclusion, our results indicated that inhibition of Skp2 either alone or in a combination with doxorubicin may hold promise in the future treatment of BCP‐ALL.